Anatomical location of the mental foramen and presence of accessory foramina through cone beam computed tomography analysis in an Ecuadorian population - Albán Saltos , Bryan Ismael (2024)
Objectives: To establish the anatomical location and characteristics of the mental foramen and the presence of accessory foramina through the evaluation of cone beam computed tomography in an Ecuadorian population. Materials and Methods: A total of 203 tomographies scans of adult patients (90% dentate and 10% edentulous) of both sexes (100 men and 103 women) aged between 20 and 65 years were analyzed. The scans were collected as a convenience sample from the UDICIS Professional Development Center, the Clinic of the University of the Hemisferios, and the private clinic Buccal Dental Studio in Quito, Ecuador. The variables studied in the transaxial plane were analyzed through 1 mm slices and 0.5 mm intervals. Results: The location of the mental foramen was predominantly found along the longitudinal axis of the second premolars on both the right and left sides, according to the classification by Al Jasser & Nwoku, in position IV (45.81%, 46 men and 47 women), followed by positions III, V, II, and VI. Regarding the size of the mental foramen, the size of 2 mm to 2.99 mm predominated in both sexes (n=85: 41.87%). The prevalence of accessory foramina was 39%. Conclusions: The mental foramen was located on average 13.65 mm above the mandibular base and 15.1 mm from the foramen to the alveolar ridge. Its most frequent location was below the axis of the second lower premolar (position IV). The oval shape predominated, with a size ranging from 2.0 mm to 2.99 mm. Accessory foramina were found in 39% of the cases.